Factors associated with pathways toward concurrent sex work and injection drug use among female sex workers who inject drugs in northern Mexico. (5th October 2012) - Morris, Meghan D.; Lemus, Hector; Wagner, Karla D.; Martinez, Gustavo; Lozada, Remedios; Gómez, Rangel María Gudelia; Strathdee, Steffanie A.
Abstract Aims To identify factors associated with time to initiation of (i) sex work prior to injecting drugs initiation; (ii) injection drug use prior to sex work initiation; and (iii) concurrent sex work and injection drug use (i.e. initiated at the same age) among female sex workers who currently inject drugs (FSW–IDU). Design Parametric survival analysis of baseline data for time to initiation event. Setting Tijuana and Ciudad Juarez situated on the Mexico–US border. Participants A total of 557 FSW–IDUs aged ≥18 years. Measurements Interview‐administered surveys assessing context of sex work and injection drug use initiation. Findings Nearly half (n = 258) initiated sex work prior to beginning to inject, a third (n = 163) initiated injection first and a quarter (n = 136) initiated both sex work and injection drug use concurrently. Low education and living in Ciudad Juarez accelerated time to sex work initiation. Being from a southern Mexican state and initiating drug use with inhalants delayed the time to first injection drug use. Having an intimate partner encourage entry into sex work and first injecting drugs to deal with depression accelerated time to initiating sex work and injection concurrently. Early physical abuse accelerated time to initiating sex work and injection, and substantially accelerated time to initiation of both behaviors concurrently. Conclusions Among female sex workers who currently inject drugs in two Mexican–US border cities, nearly half appear to initiate sex work prior to beginning to inject, nearly one‐third initiate injection drug use before beginning sex work and one‐quarter initiate both behaviors concurrently. Predictors of these three trajectories differ, and this provides possible modifiable targets for prevention.